Определение энергетического потенциала процесса стабилизации нефти с помощью пинч-анализа - Ульев, Леонид Михайлович; Кержакова, Марина Александровна (НТУ "ХПИ", 2013)
В данной работе рассматривается технологический процесс стабилизации нефти на одноколонной установке. Актуальность темы обусловлена тем, что рост цен на энергию побуждает экономнее использовать энергоресурсы с тем, чтобы уменьшить общие расходы. При помощи пинч-метода можно снизить потребление энергии на 37 МВт.

This article focuses on the possible integration of the heat in the process of rectification of ethanol-water. Was made the analysis of grid chart of the process, built a new grid diagram and a new technological scheme of the reconstruction of the heat exchange system using the methods of pinch analysis. As a result of the proposed project from the consumption of thermal energy and cooling water may completely refuse. The payback period is 3 months.
Keywords: пинч-метод; энергосбережение; составные кривые; технологический процесс; thermal integration; rectification; grid diagram; pinch